Memória e identidade da comunidade remanescente de quilombo “São Miguel” representada na boneca Abayomi - Rigon, Janaina Ideli (2023)
The present research is linked to the remembering of African memory and identity in the remaining quilombo community "São Miguel," located in the municipality of Restinga Sêca, which is an integral part of the Fourth Colony UNESCO World Geopark. Since the Federal Constitution of 1988, quilombola communities have conquered visibility, providing Afro-Brazilian descendants with a prominent place in the Brazilian political and social scene. In this context, the study and understanding of the main legislations are of importance to the people residing in the remaining quilombo community "São Miguel" and other localities. This research was developed in the Cultural Heritage Postgraduate Program at the Federal University of Santa Maria, in the area and research line of History and Cultural Heritage. It is anchored in a qualitative and quantitative approach, including bibliographic research, data collection, interviews with women/mothers/grandmothers from the locality, photographic records, maps, among others. Linking the theme of the quilombo community in the municipality of Restinga Sêca/RS to its historical, social, and cultural context, as well as to material and immaterial heritage and belonging to a Geopark. The product of this study is a toy, the Abayomi doll, which was produced with the students of the preschool classes A and B of the Municipal Elementary School Manuel Albino Carvalho, located in the study community and distributed among them, as well as a book with a step-by-step guide on making the Abayomi doll.